ENHANCING STUDENTS’ SPEAKING PERFORMANCE THROUGH A DAY IN MY LIFE CONTENT’ ON - Huka, Britshy Rosanadya; Basikin, Basikin; Ximenes, Adalciza Agusta; Manafe, Thedy Hardi; Relmasira, Mega Victoria; Kawai, Santi; Kesaulija, Anggelvania Liany (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2024)
This study investigates the effectiveness of using